2019
DOI: 10.1016/j.celrep.2019.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Dormant and Active Hematopoietic Stem Cells by G0 Marker Reveals Dormancy Regulation by Cytoplasmic Calcium

Abstract: Highlights d G 0 marker (G 0 M) discriminates between dormant (G 0 M high ) and active (G 0 M low ) HSCs d Active (G 0 M low ) HSCs exhibit higher CDK4/6 activity than dormant (G 0 M high ) HSCs d [Ca 2+ ] c high HSCs have higher bone marrow reconstitution ability than [Ca 2+ ] c low HSCs d Upregulation of [Ca 2+ ] c enhances bone marrow reconstitution ability of HSCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 72 publications
1
52
1
Order By: Relevance
“…The study also highlighted how intracellular calcium levels regulate calpain and subsequently the activity of TET (Ten-eleven Review translocation) enzymes for HSC maintenance. However, high concentration of cytoplasmic calcium has also been associated with dormant HSCs (Fukushima et al, 2019).…”
Section: Regulation Of Ros In Adult Hscsmentioning
confidence: 99%
“…The study also highlighted how intracellular calcium levels regulate calpain and subsequently the activity of TET (Ten-eleven Review translocation) enzymes for HSC maintenance. However, high concentration of cytoplasmic calcium has also been associated with dormant HSCs (Fukushima et al, 2019).…”
Section: Regulation Of Ros In Adult Hscsmentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted September 27, 2021. ; https://doi.org/10.1101/2021.09.27.461900 doi: bioRxiv preprint 0.01), whereas CPA3, ABCA1, CDK6 and IRF8 were highly DEGs in PLXDC2 -HSCs (FDR < 0.01) (Figures 5A and 5B). Interestingly, CDK6 expression has been shown to mark active HSCs in mouse and human studies (Laurenti et al, 2015;Cabezas-Wallscheid et al, 2017;Fukushima et al, 2019) and IRF8 is a differential marker for myeloid cells (Kurotaki et al, 2013;Kurotaki et al, 2018). The gene expression data therefore suggest that PLXDC2 -HSCs express a more differentiated gene signature than PLXDC2 + HSCs.…”
Section: Plxdc2 + Hscs Express More Hsc Signature Genes Than Plxdc2 -Hscsmentioning
confidence: 99%
“…We introduced G0 marker (G0M) to a mouse CML-like model to visualize quiescent CML LSCs. We retrovirally overexpressed BCR-ABL1 fusion gene in BM cells from 5FUtreated G0M mice, in which Cre-inducible G0M in a Rosa26 allele is regulated by Vav1-Cre 44 , and then injected the cells into lethally irradiated wild-type recipient mice to develop mouse CML-like disease (Figure 1A). CML derived from BM cells carrying G0M was developed in about 3 weeks, and imatinib treatment prolonged the survival of leukemic mice (Figure 1B), ensuring that G0M did not affect CML development or imatinib treatment.…”
Section: Identification Of CML Lscs By G0 Marker and Cd27mentioning
confidence: 99%
“…Previously we reported that G0 marker (G0M), a fusion protein between the fluorescent protein mVenus and p27K-, which is a p27 mutant lacking cyclin dependent kinase (Cdk) inhibitory activity, is a useful tool for visualizing the quiescent states of conventional long-term HSCs, and the stemness of the cells was correlated with the intensity of G0M 43,44 . In the present study, we applied G0M to identify and visualize quiescent CML LSCs.…”
Section: Introductionmentioning
confidence: 99%